The Map of Jihad Meaning Among Junior High School Students in Padang - Novizal Wendry; Sefriyono Sefriyono; M Yusuf (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
This present research aims to explore the meaning of jihad among Muslim youths in the context of junior high school students in Padang. Muslim youths at this level are considered to have unique characteristics in expressing diversity, including in the interpretation of jihad. As a qualitative research, it gathered the relevant data through series of survey of the perception of students on jihad and its rationale, as well as their sources of knowledge on the issue. The interlocutors include students in several junior high school in Padang, including Thawalib Boarding School, MTsN 5, SMP 24, MTSs Tarbiyah Islamiyah, MTSs Bustanul Ulum, and SLTP Muhammadiyah 7. This research discovered that there were five types of definitions of the meaning of jihad proposed by the respondents of the research. First, jihad was seen as earnest in worship, secondly; jihad was meant as being committed to work, third; jihad was interpreted as devotion to parents, fourth; jihad was interpreted as an effort to spread Islamic teachings and the fifth; Jihad was defined as a war against infidels. There were several sources which affected the way respondents interpreted the meaning of jihad, for instance, Islamic teacher (ustāż) around 85%, Quran teacher 73%, parents 59%, religion teacher in elementary school 54%, and junior high school teacher for 51%.